AN IRREDUCIBLE VARIANT OF COMPLEX UNSTABLE INTERTROCHANTERIC FRACTURE-A TECHNIQUE FOR OPEN REDUCTION - F, Normughni; Ahmad, Mohammed harris; Kunalan, Shival Sasidaran; Mohamad, Fazir (International Journal of Allied Health Sciences, 2021)
The care of patients with intertrochanteric fractures has advanced dramatically since the advent of internal fixation. However, the differences in failure rates between stable and unstable intertrochanteric fracture patterns have recently been emphasized. The goal of management of any hip fractures in the elderly is to restore mobility safely, efficiently while minimizing the risk. Whilst reduction by closed manipulation and traction remains the gold standard, difficulty in achieving anatomic alignment with complex unstable fracture remain the obstacle during surgery. Open reduction in proximal femoral nail insertion to achieve good reduction, optimal positioning lag screws is an option for the proximal femoral nail procedure. This article reports a 79-year-old lady presented with pain over the left hip after slipped and fall. Upon examination, there was some ecchymosis on the left greater trochanteric region, tenderness, and inability to actively raise the left lower limb. Radiographic evaluation showed complex unstable intertrochanteric fracture of left femur. We treated this complex unstable fracture using proximal femoral nail with modified open reduction technique. Attempts at closed reduction were not possible by any manoeuvre of rotation necessitating open reduction. The approach for open reduction should expose only as much of the fracture zone as necessary to achieve reduction. Periosteum elevator, bone spike and bone hook can be used to obtain reduction. Good alignment and implant position were achieved under image intensifier guidance. In conclusion, if one encounters this fracture pattern in practice, do not spend time on repeated attempts for closed reduction. Draping the patient in situ, using percutaneous joystick or minimal open reduction is fairly adequate. Satisfactory reduction in complex unstable intertrochanteric fractures could be achieved using this simple technique.